2015
DOI: 10.21548/36-3-971
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Copper Ions on Colour in Extracts of Cabernet Sauvignon and Sangiovese Skins Under Wine-like Conditions

Abstract: Pigment-metal complexes are generally not considered to play significant roles in grape and wine colour. However, to the best of my knowledge, this hypothesis has never been investigated. In this work, grape skin extracts (cultivars Sangiovese and Cabernet Sauvignon) were allowed to react with copper sulphate aqueous solutions at different concentrations. High, and toxic, copper additions produced significant absorption increases in the green spectral region (corresponding to the typical absorption band of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In this study, considering that malvidins cannot chelate metals ( Boulton, 2001 ; Dixon et al, 2005 ), minor anthocyanidins in the form of cyanidin, delphinidin, and petunidin primarily contribute to metal chelation. For example, Rustioni (2015) suggested that non- ortho dihydroxyl groups and copigments could have a considerable effect on grape AC added with Cu(II) (Sangiovese and Cabernet Sauvignon) and found that higher concentrations of Cu(II) resulted in hyperchromic and slight hypsochromic shifts, which were consistent with our results.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, considering that malvidins cannot chelate metals ( Boulton, 2001 ; Dixon et al, 2005 ), minor anthocyanidins in the form of cyanidin, delphinidin, and petunidin primarily contribute to metal chelation. For example, Rustioni (2015) suggested that non- ortho dihydroxyl groups and copigments could have a considerable effect on grape AC added with Cu(II) (Sangiovese and Cabernet Sauvignon) and found that higher concentrations of Cu(II) resulted in hyperchromic and slight hypsochromic shifts, which were consistent with our results.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, the effect of metal chelation on the color stability of AC in response to pH depends primarily on the metal cation used and the type of anthocyanidin. Malvidin is the major anthocyanidin found in grapes representing 60∼70% of the total AC ( Rustioni, 2015 ). In this study, considering that malvidins cannot chelate metals ( Boulton, 2001 ; Dixon et al, 2005 ), minor anthocyanidins in the form of cyanidin, delphinidin, and petunidin primarily contribute to metal chelation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation